Efficacy of adjunctive measures used to assist pulmonary vein isolation for atrial fibrillation: a systematic review. (January 2017) - Nair, Girish M.; Raut, Roshan; Bami, Karan; Nery, Pablo B.; Redpath, Calum J.; Sadek, Mouhannad M.; Green, Martin S.; Birnie, David H.
Abstract : Purpose of review: Pulmonary vein reconnection leading to recurrence of atrial arrhythmias after pulmonary vein isolation (PVI) for atrial fibrillation remains a significant challenge. A number of adjunctive measures during PVI have been used to attempt to reduce pulmonary vein reconnection and recurrence of atrial arrhythmias. We performed a systematic review of the literature and meta-analysis of studies evaluating the efficacy of adjunctive measures used during PVI in reducing recurrent atrial arrhythmias. Recent findings: Our literature search found four interventions that met the prespecified definition of adjunctive measure: adenosine testing post-PVI, contact force–guided PVI, pacing inexcitability of the ablation line during PVI and additional ablation based on the computed tomography thickness of the pulmonary vein–left atrial appendage ridge. Sixteen studies enrolling 3507 patients met all inclusion and exclusion criteria. PVI performed with adjunctive measures was shown to reduce the 1-year recurrence rate of atrial arrhythmias. The point estimate for the combined relative risk of atrial arrhythmia recurrence was 0.56 [95% confidence interval (CI): 0.43–0.73; P value <0.001] in the PVI with adjunctive measures group. Summary: PVI for atrial fibrillation assisted by adjunctive measures results in clinically significant reduction of recurrent atrial arrhythmias. Additional research is required to assess the relative efficacy of individual or combined adjunctive strategies used during PVI for atrial fibrillation. Abstract : Supplemental Digital Content is available in the text